Influence of Convenience, Price, and Social Media on Consumer Behavior in the Digital Era - Syirah, Amelia; Sunarto, Andang; Efrianto, Eeng Juli (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to determine the influence of convenience, price, and social media on consumptive behavior in the digital era. Methodology: The research employs a quantitative approach, using primary data collected through a Google Form questionnaire distributed to 93 respondents. Data analysis was performed using multiple linear regression with SPSS version 26. Results: The F-test results show that the variables of convenience, price, and social media collectively have a significant effect on consumptive behavior, with a significance value of 0.000 < 0.05. The t-test results confirm that each independent variable significantly influences consumptive behavior, with significance values below 0.05. Findings: The combined influence of convenience, price, and social media accounts for 30.7% of the variance in consumptive behavior, indicating a moderately strong effect on students’ purchasing habits. Novelty: This study provides valuable insights into how digital-era factors like convenience, price, and social media shape consumptive behavior among students, a topic not widely explored in current research. Originality: The study is original in its focus on students’ consumptive behavior in the context of the digital era, incorporating modern factors like social media into the analysis. Conclusions: Convenience, price, and social media significantly influence consumptive behavior, with a moderate effect on students’ purchasing decision. Type of Paper: Empirical research paper.